Pengembangan Website Pojok Statistik Institut Keguruan dan Teknologi Larantuka Menggunakan Metode User Centered Design - Melky Falenchyl; Dominikus Boli Watomakin; Bernadete Deta (STMIK Banjarbaru, 2026)
The Statistics Corner website of the Institut Keguruan dan Teknologi Larantuka (IKTL) currently lacks the capability to provide interactive statistical information services or data presentations that are easily understood by users. This study aims to develop the Pojok Statistik website using the User-Centered Design (UCD) method by integrating a